Untreated depression and non-medical use of prescription pain relievers: findings from the National Survey on Drug Use and Health 2008-2014. Issue 1 (2nd January 2019) - Carrà, Giuseppe; Bartoli, Francesco; Galanter, Marc; Crocamo, Cristina
ABSTRACT: Objectives : Despite growing concerns for non-medical use of prescription pain relievers (NMUPPRs), little is known about the role of comorbid, untreated depressive disorders. Methods : We examined past year rates of NMUPPRs and major depressive episode (MDE), using data between 2008 and 2014 from the National Survey on Drug Use and Health for both youths (12–17 years) and adults (18 or older). Prevalence estimates with 95% confidence intervals were computed. Stratified analyses and generalized linear models were run to examine the association between NMUPPRs and MDE, controlling for treatments received for mental health and/or substance misuse. In order to explore whether MDE effect might change by treatment received, a model with an interaction term including MDE and treatment was fit. Results : Among respondents, about 9% (youths) and 7% (adults) reported past year MDE and about 6% (youths), and 4% (adults) NMUPPRs. About 1.2% (youths) and 0.7% (adults) reported both MDE and NMUPPRs. Those with past year MDE were more likely to report NMUPPRs (RR, 95%CI: 2.60, 2.42–2.80, and 2.64, 2.47–2.82, for youths and adults). Considering the any treatment/MDE interaction on NMUPPRs, MDE risk ratio for subjects who received some treatment (youths: adjusted risk ratio (ARR) = 1.15; adults: ARR = 1.25) was about 70–80% as compared with their untreated counterpart (youths: ARR = 1.57; adults: ARR = 1.54). The likelihood of reporting NMUPPRs amongst respondents who did not receive any treatment was higher for those with past year MDE (main effect: youths ARR = 1.57, p < 0.001; adults ARR = 1.54, p < 0.001). Conclusion : Unrecognized and untreated depressive disorders should be considered for prevention, treatment, and policy implications in order to tackle NMUPPRs epidemic.